Public opinions in Bioethics - Giliberti, Mauro; Refolo, Pietro (Medicina e Morale, 2023)
The phenomenon of public opinion is one of the fundamental figures in today's democratic processes, especially within the context of the increasingly desired deliberative perspective. Even in reference to bioethical issues, parliaments have often to legislate under the pressure of public opinion. Who or what is more precisely "public opinion"? The first aim of this article is cognitive: through a brief historical reconstruction of the concept of "public opinion", its typification, and an explication of the main theories of its formation, we will try to capture complexity and ambiguity of this concept. Second, we will extrapolate the main features of the modern concept of deliberative democracy. Third, we will briefly analyze the characteristics of information in bioethics. The final aim of the article is to try to draw practical indications for public opinion formation on bioethical issues in the context of journalistic communication, having the deliberative model of democracy as a background.